(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the distinction between data and information, two terms often used interchangeably. While data refers to raw, unprocessed facts and statistics, information is data that has been processed, organized, and given meaning. The article emphasizes how data transforms into valuable information through context, structure, and analysis, making it useful for decision-making. By understanding this difference, individuals and organizations can better leverage data, turning it into actionable insights that drive meaningful outcomes.